A population‐level analysis of 5620 recipients of multiple in‐hospital cardiopulmonary resuscitation attempts. Issue 1 (6th December 2013) - Kazaure, Hadiza S.; Roman, Sanziana A.; Sosa, Julie A.
<x xml:space="preserve">Abstract</x> BACKGROUND There is a paucity of data examining the epidemiology of recipients of multiple in‐hospital cardiopulmonary resuscitation (CPR) attempts, and their outcomes. METHODS Data source: Nationwide Inpatient Sample, 2000 to 2009. Patient characteristics, survival to discharge, discharge disposition, and cost of hospitalization of patients who had 1 versus multiple (>1) CPR attempts were compared using bivariate and multivariate methods. RESULTS Of 166, 519 hospitalized CPR recipients, 3.4% had multiple CPR attempts. Compared with 1‐time CPR recipients, those undergoing multiple CPR were younger (age <65 years; 37.3% vs 42.5%, respectively), more often nonwhite (34.2% vs 41.4%), and commonly treated in nonteaching hospitals (58.0% vs 64.5%; all P < 0.001). Survival to discharge decreased by >40% for each additional CPR attempt (23.4% vs 11.9%, and 6.7% for 1, 2, and ≥3 CPR attempts, respectively; P < 0.001). After multivariate adjustment, multiple CPR was independently associated with a lower survival to discharge (odds ratio: 0.41, 95% confidence interval: 0.37‐0.44, P < 0.001). Recipients of multiple CPR were more likely to be discharged to destinations other than home (80.7% vs 70.1%, P < 0.001); 1 in 15 survivors of multiple CPR were discharged to hospice (6.8%), compared with 1 in 23 patients (4.3%) who had 1 CPR (P = 0.002). The average cost per day of hospitalization was higher for patients who had multiple CPR versus 1 CPR (4484.60 vs 3581.40, P < 0.001). CONCLUSIONS Recipients of multiple in‐hospital CPR attempts are more likely to be younger, nonwhite, and treated in nonteaching hospitals. Survival to discharge is significantly worse, and the cost of hospitalization is considerably higher for these patients. Journal of Hospital Medicine 2014;9:29–34. © 2013 Society of Hospital Medicine